Adnexal tumours in the menopausal period – analysis of diagnoses and histological verification from the database of the Department of Gynaecology and Menopausal Diseases in Polish Mother’s Memorial Hospital, Research Institute in Łódź - Jędrzejczak, Sławomir; Zając, Agnieszka; Stachowiak, Grzegorz; Dębowski, Marcin; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2007)
The treatment of adnexal tumours in women in the menopausal period remains a challenge for every gynaecologist coping with operative procedures. The opinion that the diagnosis of adnexal tumour in women after menopause is an indication for operation (=high oncological risk) is still obligatory. However, it is proper to know that most (>80%) of the adnexal lesions being extirpated in menopausal women (which was also observed in this study) are non-neoplastic tumours or benign neoplasms. An important role in the diagnostic-therapeutic process is played by a properly performed transvaginal ultrasonography permitting one to choose the way and the extent of operative management – laparotomy, laparoscopy or fine-needle biopsy.